Individual, familial and extrafamilial factors of suicidal ideation among adolescents in Selangor, Malaysia - Wu, Shin Ling (2016)
Suicide phenomenon has become the leading cause of death worldwide especially among adolescents. Prior to committing suicide, suicidal ideation occurs. Suicidal ideation refers to the thoughts or desires to end one’s own life. In Malaysia, suicide cases are increasing rapidly, yet little research has been done especially among adolescents. In addition, past research mostly focus on psychiatric patients in clinical settings. Therefore, the current study was conducted to investigate the individual, familial and extrafamilial factors of suicidal ideation among adolescents in Selangor, Malaysia. This study is quantitative in nature and utilized a descriptive and correlational research design. Survey method was used to collect the data. A total of 682 school-going adolescents aged 14 to 17 were recruited as respondents by using multistage cluster sampling technique. Data from the self-administered questionnaires were analyzed using SPSS. Six instruments were administered in this study namely the Positive and Negative Suicide Ideation Inventory, Network of Relationships Inventory-Relationship Quality Version, Children’s Hope Scale, Perceived Stress Scale, General Self-efficacy Scale, and Satisfaction with Life Scale. Descriptive, bivariate and multivariate statistics were used in data analysis to address the specific objectives of the study. This study found that 60% of the respondents reported having suicidal thoughts. Findings from the ANOVA tests showed that there were no ethnic groups differences in suicidal ideation among adolescents. Moreover, the independent samples t-test analysis indicated no sex differences in suicidal ideation among adolescents. The independent samples t-test analysis also revealed that there were significant differences among adolescents with and without suicidal ideation in terms of hope, stress, self-efficacy, life satisfaction, maternal, paternal, peer and teacher relationship. Adolescents with suicidal ideation had lower level of hope, self-efficacy and life satisfaction. They also experienced higher level of stress, and more negativity with their mother, father, peer, and teacher. Binary logistic regression highlighted that stress, life satisfaction, paternal and peer relationship were the unique predictors of suicidal ideation among adolescents. Stress was the strongest predictor, followed by life satisfaction, peer relationship, and lastly paternal relationship. Parallel multiple mediator analysis using SPSS PROCESS macro by Preacher and Hayes (2004) indicated that only stress partially mediated the relationships between maternal, paternal, and peer relationship with suicidal ideation. This showed that maternal, paternal and peer relationships not only directly affect suicidal ideation, but also indirectly affect suicidal ideation through stress. Stress appeared to be the only mediator in this study indicating stress as the most important factor of suicidal ideation among adolescents as stress explained the relationship between maternal, paternal and peer relationships with suicidal ideation. The integrated investigation on the individual factors (hope, stress, self-efficacy and life satisfaction), familial factors (maternal and paternal relationship), and extrafamilial factors (peer and teacher relationship) provide insights on the factors affecting suicidal ideation among adolescents. The findings from this study implied the seriousness of suicidal ideation and the critical contribution of stress in suicidal ideation among adolescents in Selangor, Malaysia. Both familial and extrafamilial factors may also contribute to suicidal ideation. Therefore, to reduce suicidal ideation among adolescents, individuals and professional working with adolescents must focus on stress management in order to provide adolescents with the necessary skills needed to survive in this challenging society. Parents also need to be equipped with the appropriate skills to establish a more quality relationship with their children. Lastly, adolescents need to improve their social skills to aquire a better relationship with their peers.